2005
DOI: 10.1029/2003jb002603
|View full text |Cite
|
Sign up to set email alerts
|

Irregular earthquake cycle along the southern Tianshan front, Aksu area, China

Abstract: [1] A long deformation record ($16.5 ka) showing nonsteady earthquake recurrence is established for the Aksu thrust (Tianshan, China) on the basis of cosmogenic 10 Be dating of faulted surfaces. Topographic leveling across the Aksu fault scarp indicates up to $10 m uplift across a moraine abandoned $16.5 ka and similar uplift of $6 m across two inset surfaces yielding ages of $12.5 and $5 ka. Successively smaller uplifts of terraces younger than 5 ka indicate that three or more major earthquakes occurred duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 69 publications
2
24
0
Order By: Relevance
“…Line length calculations along the highest terrace indicate 11 m of shortening across the 8‐km‐long terrace. Similar broad terrace levels from the Kuqa Basin ∼1000 km east have been dated at 12.5 ka [ Hubert‐Ferrari et al , 2005]. Using 12.5 ka as an estimated age for the terrace, shortening of ∼1 mm/a is calculated for the Atushi Anticline.…”
Section: Structures and Shorteningmentioning
confidence: 68%
“…Line length calculations along the highest terrace indicate 11 m of shortening across the 8‐km‐long terrace. Similar broad terrace levels from the Kuqa Basin ∼1000 km east have been dated at 12.5 ka [ Hubert‐Ferrari et al , 2005]. Using 12.5 ka as an estimated age for the terrace, shortening of ∼1 mm/a is calculated for the Atushi Anticline.…”
Section: Structures and Shorteningmentioning
confidence: 68%
“…These cycles last on the order of 15 -200,000 model years. Our models, along with other numerical [Naylor and Sinclair, 2007] and analog models [Hoth et al, 2006; and some well dated examples from active orogens [Masaferro et al, 2002;Hubert-Ferrari et al, 2005;Sinclair et al, 2005], suggest that transient accommodation of strain may be common. Thus, caution should be applied when extrapolating long-term slip rates from varying temporal scales.…”
Section: Discussionmentioning
confidence: 99%
“…Cosmogenic 10 Be dating along the Asku Fault (Tian Shan, China) reveals a record of activity followed by a long quiescence (at least 7.5 ka) and recent activity over the past 5 ka [Hubert-Ferrari et al, 2005]. Masaferro et al [2002] showed that the Neogene-Quaternary growth of the Santaren anticline (Cuban fold and thrust belt) is characterized by several tectonic uplift pulses of different duration and intensity, interrupted by periods of variable duration in which no fold growth occurred.…”
Section: Thrust Cycling Within the Models And Naturementioning
confidence: 99%
“…It is one of the largest and most active intracontinental mountain ranges (Figure 3) [ Avouac et al , 1993; Molnar and Deng , 1984]. Up to 20 mm/yr of shortening [ Abdrakhmatov et al , 1996; Reigber et al , 2001; Molnar and Ghose , 2000] is accommodated in thrust belts on both sides and within the range [ Allen et al , 1999; Burchfiel et al , 1999; Burbank et al , 1999; Chen et al , 2002; Thompson et al , 2002; Hubert‐Ferrari et al , 2005b]. In the eastern part of the southern Tian Shan between 80°30′ and 85°E, the main locus of deformation is the 350‐km‐long Kuche fold‐and‐thrust belt that deforms an 8‐ to 10‐km‐thick Triassic to Recent sequence of continental strata [ Yin et al , 1998].…”
Section: Tectonic Setting Of Active Foldingmentioning
confidence: 99%